Pituitary Apoplexy in Pregnancy: What do We Know? - Mariana Alves Patrício de Oliveira Gamito; Njila Yakalage Barreira Amaral; Carla Francisco Rodrigues; Joana Mariz Ribeiro; Sílvia Guerra (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Pituitary apoplexy refers to a rare clinical syndrome consisting of signs and symptoms that occur due to rapid expansion of the contents of the sella turcica. It can occur spontaneously or associated with pituitary tumors. It can have a broad clinical spectrum, but usually presents with severe headache, visual impairment and hypopituitarism. Sudden onset of symptoms associated to imagiologic confirmation makes the diagnosis. Surgical treatment is advised when there is important compression of the optic tract. We present a case report and a review of the literature on pituitary apoplexy in pregnancy. The cases were reviewed to obtain information on maternal characteristics, clinical presentation, diagnostic studies, therapeutic modalities and maternal and fetal outcomes. Our review found 36 cases of pituitary apoplexy in pregnancy. Most of the cases occurred in the second trimester of pregnancy and headache was the most frequent symptom at presentation. Surgical therapy was required in more than half of the patients. In what respect maternal and fetal outcomes, there were 3 cases of preterm delivery and one case of maternal death. Our clinical case and literature review reinforces the importance of an early diagnosis to avoid potential adverse consequences.